Legal analysis of the status and content of general election commission decision number 1774 of 2024 in the election of the mayor of Banjarbaru - Muhammad Ridho Taufiq; Maksum Maksum; Abdul Hamid (International Journal of Law, Environment, and Natural Resources, 2026)
This article aims to analyze the legal position and substantive content of General Elections Commission Decision Number 1774 of 2024 within the regulatory system of regional head elections, focusing on the 2024 Banjarbaru mayoral election. This study addresses a gap in electoral law scholarship, which has primarily examined election administration and dispute resolution but has given limited attention to the legal status of General Elections Commission Decisions that contain general and continuously applicable norms. The legal issue emerged when one candidate pair was disqualified after ballot printing, yet the election was not transformed into a single-candidate election using the empty-column mechanism. Instead, the General Elections Commission applied a technical provision declaring votes for the disqualified candidate pair invalid. This research employs normative legal research using statutory, conceptual, and case approaches. The study finds that Decision Number 1774 of 2024 cannot be classified as a beschikking because it lacks individual, concrete, and final characteristics. However, it also cannot be regarded as a regulation (regeling) because its authority is not derived from legislative delegation. The decision is more appropriately positioned as a beleidsregel or technical policy rule. Furthermore, Point 5 of the Decision conflicts with Article 54C of the Regional Head Election Law, which requires the empty-column mechanism when only one candidate pair remains. This study contributes a novel perspective by examining the hybrid legal character of KPU Decisions and clarifying the limits of electoral administrative discretion in protecting citizens’ meaningful voting rights.